Signal Pathways Involved in the Interaction Between Tumor-Associated Macrophages/TAMs and Glioblastoma Cells - Liu, Xiaojin; Liu, Yuan; Qi, Yiwei; Huang, Yimin; Hu, Feng; Dong, Fangyong; Shu, Kai; Lei, Ting (Frontiers in Oncology, 2022)
It is commonly recognized, that glioblastoma is a large complex composed of neoplastic and non-neoplastic cells. Tumor-associated macrophages account for the majority of tumor bulk and play pivotal roles in tumor proliferation, migration, invasion, and survival. There are sophisticated interactions between malignant cells and tumor associated-macrophages. Tumor cells release a variety of chemokines, cytokines, and growth factors that subsequently lead to the recruitment of TAMs, which in return released a plethora of factors to construct an immunosuppressive and tumor-supportive microenvironment. In this article, we have reviewed the biological characteristics of glioblastoma-associated macrophages and microglia, highlighting the emerging molecular targets and related signal pathways involved in the interaction between TAMs and glioblastoma cells, as well as the potential TAMs-associated therapeutic targets for glioblastoma.